THE CONSTITUTIONAL PROBLEM OF PERPPU IN THE INDONESIAN LEGAL SYSTEM: TENSIONS BETWEEN EXECUTIVE AND LEGISLATIVE AUTHORITY FROM THE PERSPECTIVE OF CHECKS AND BALANCES - Indra Utama Tanjung; Arminsyah (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2026)
A Government Regulation in Lieu of Law (PERPPU) is a constitutional instrument granted to the President under Article 22 of the 1945 Constitution of the Republic of Indonesia in cases of compelling emergency. Although normatively intended as an emergency mechanism, the practice of issuing PERPPUs has sparked debate regarding the limits of their constitutionality, particularly in the context of the relationship between the executive and legislative branches of government. This study aims to analyze the constitutionality of PERPPUs within the Indonesian legal system and examine the tensions between the President and the House of Representatives (DPR) from a checks and balances perspective. This study uses normative legal methods with a statutory and conceptual approach. The analysis was conducted on constitutional provisions, Law Number 12 of 2011 concerning the Formation of Legislation, and Constitutional Court Decision Number 138/PUU-VII/2009, which defines the objective parameters of compelling emergency. The results indicate that a PERPPU is formally valid if it meets the procedures stipulated in Article 22 of the 1945 Constitution and obtains DPR approval. However, substantively, the practice of interpreting the phrase